Gender Equity in Islamic Marriage and Divorce: A Narrative Review - Lestari, Putri Ayu (Yayasan Sinergi Kawula Muda, 2024)
This narrative review examines the evolving landscape of marriage and divorce in Islamic contexts, with a focus on gender equity, legal interpretation, and socio-cultural influences. The study aims to understand the systemic barriers faced by women in initiating divorce and how legal, educational, and institutional reforms can address these challenges. Utilizing sources from Scopus, Google Scholar, JSTOR, and SpringerLink, the review analyzed literature published over the past fifteen years using keywords such as